On Process Organization in Crisis Situations with BPMN, CMMN and DMN - Sandra NIEMZ; Sven GEHRKE; Johannes RUHLAND (Communications of International Proceedings, 2021)
Unforeseen events or disruptions caused by humans or nature can have extreme effects. A current omnipresent example is the corona pandemic, which, due to the changing number of infections, repeatedly requires various adjustments. In particular, these can have an effect on various types of processes in companies which often use workflow management to organize their processes. However, it is difficult to react adequately and flexibly to unforeseen situations. The three modeling languages of the Object Management Group (OMG) BPMN, CMMN and DMN can cover different areas of process management due to their different focus. This paper therefore examines how the “Triple Crown” of the OMG can be used in crisis situations and how to adapt the processes to the given conditions. The question that remains open and needs to be analyzed in this paper is which modeling language is recommended for certain process types, crisis management and what requirement is covered by the mentioned languages.
Keywords: BPMN; CMMN; DMN; Crisis Management.